Implementation of Context Input Process Product Model on Healthy Indonesia Program Policy with a Family Approach - Ninawati, Ninawati; Sulaeman, Endang Sutisna; Tamtomo, Didik (Journal of Health Policy and Management, 2022)
Background: The Healthy Indonesia Program with a Family Approach started in 2017, has now reached the first visit coverage rate of 26.80% as of October 3, 2018, with a Healthy Family Index (IKS) value of 0.165. This figure is still far below the expected target, namely in 2019 it is expected that the visit coverage rate has reached >90% so that in 2019 an intervention plan at the community health center (puskesmas) level can be carried out in accordance with the roadmap of the Ministry of Health. This study aimed to investigate the implementation of the context input process product (CIPP) model in the healthy Indonesia program policy with a family approach.Subjects and Method: This research is a qualitative descriptive study using a sample of policy makers and implementers of the Healthy Indonesia program with a Family Approach (PIS – PK), namely: Head of Public Health Center, Head of Health Service Division of Karanganyar District Health Office, Person in Charge of Healthy Indonesia Program, implementer of PIS – PK visits, and the surrounding community. The research was conducted in August 2021. Data were collected by means of document review, in-depth interviews, focus group discussions (FGD), and participatory observations. Data is presented in analytical descriptive form.Results: Data were collected from 16 research respondents. In the input aspect, the implementation of PIS PK is supported by sufficient human resources, although there are still gaps in the fulfillment of types of positions. Financial support, infrastructure, methods, implementation time and cross-sectoral support look very good and in accordance with the mandate of the Minister of Health 39 of 2019 concerning PIS PK. There are still problems in the application of healthy families, making the PIS PK output results not in accordance with manual calculations, so that family interventions both individually and in groups cannot be carried out optimally. Not all puskesmas have also implemented total coverage in the implementation of PIS PK, nor have all puskesmas used IKS value data as one of the inputs in planning puskesmas in the form of RUK and RPK.Conclusion: The Healthy Indonesia Program (PIS PK) in Karanganyar Regency can be implemented well in terms of context, input and process, but it is still not optimal in the aspect of output because of obstacles in the application of healthy families and the output of PIS PK has not been fully used as a basis for planning at the puskesmas level.Keywords: : context, input, process, product, Healthy Indonesia ProgramCorrespondence: Ninawati. Masters Program in Public Health, Universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java. Email: dimniasna@yahoo.com. Mobile: 08112632356.Journal of Health Policy and Management (2022), 07(01): 34-45https://doi.org/10.26911/thejhpm.2022.07.01.04.